Pengaruh Pelatihan K3, Kepatuhan K3, dan Gaya Kepemimpinan Terhadap Tingkat Kecelakaan Kerja : Studi pada PT. XYZ - Syahrani Fitria; Koen Hendrawan (STIKes Ibnu Sina Ajibarang, 2025)
This study was conducted to analyze the effect of occupational safety and health (OHS) training, OHS compliance, and leadership style on the workplace accident rate among employees of PT. XYZ. Workplace accidents remain a significant problem in the industrial sector, thus this study seeks to provide a deeper understanding of the factors that can reduce this risk. The research method used was a quantitative survey approach, where primary data were obtained by distributing questionnaires to 40 respondents selected using a non-probability sampling technique with a purposive sampling method. The analysis techniques used in this study were descriptive analysis and multiple linear regression with the help of SPSS software version 25. The use of regression analysis allows researchers to determine the strength and direction of the relationship between independent and dependent variables. The results show that OHS compliance has a significant influence on the workplace accident rate. This confirms that compliance with occupational safety and health procedures can minimize the risk of accidents. Meanwhile, OHS training and leadership style did not show a significant influence on workplace accidents. This finding indicates that training programs and leadership style may not directly reduce workplace accidents unless they are consistently implemented and supported by strong compliance. Thus, OHS compliance is a key factor in creating a safe and productive work environment. This research provides a practical contribution for companies to focus safety management policies more on improving worker compliance with OHS regulations. Furthermore, the results of this study can serve as a reference for further research in different industrial contexts.